2014
DOI: 10.1021/la404988d
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticle Organization through Photoinduced Bulk Mass Transfer

Abstract: A series of dipolar triphenylaminoazo derivatives, with largely distinct charge transfer and glass transition temperatures, has been synthesized. Their photomigration capability in the solid state to form surface relief gratings (SRGs) under interferential illumination has been investigated with respect to their photochromic properties and showed a prevailing influence of the bulkiness of the azo substituent. The azo mass transfer was utilized to efficiently photoalign 200 nm polystyrene nanoparticles along th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
28
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 49 publications
0
28
0
Order By: Relevance
“…To extract the rate constants (k i ) associated with the dynamics of the birefringence measurements during both the orientation and relaxation processes, biexponential fitting laws were used as already reported for the photochromic studies in thin films. 35,49,52 The orientation processes are described by eq 2 while the relaxation is described by eq 3.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…To extract the rate constants (k i ) associated with the dynamics of the birefringence measurements during both the orientation and relaxation processes, biexponential fitting laws were used as already reported for the photochromic studies in thin films. 35,49,52 The orientation processes are described by eq 2 while the relaxation is described by eq 3.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…To contextualize this observation, UV–vis and Raman spectroscopy measurements on pDR1a have shown that the fraction of cis isomers in the photostationary state decreases when applying an increasing hydrostatic pressure but that some photoisomerization remains possible even at applied pressures as high as 1 GPa . This capability of macroscopic material transport can be used to move passive objects, as was shown for polystyrene nanoparticles on the surface of an azobenzene‐containing glassy film …”
Section: All‐optical Mass Transport Of Materialsmentioning
confidence: 91%
“…A polymer film containing azobenzene, which gives a liquid‐crystalline structure and dichroism to the polymer, showed photoinduced bending perpendicular to the direction of polarization . Another representative example is the system using polarized light with an interference fringe to form a grating relief on the surface of azobenzene polymers . These deformations of polymers containing azobenzene were caused by trans – cis isomerization, which changes the degree of orientation in the liquid‐crystalline structure.…”
Section: Figurementioning
confidence: 99%
“…[19] Another representative example is the system using polarized light with an interference fringe to form ag rating relief on the surface of azobenzene polymers. [20,21] These deformationso fp olymers containing azobenzene werec aused by trans-cis isomerization, which changes the degree of orientation in the liquid-crystalline structure.Amphiphilic diarylethene 1 forms micrometer-sized spherical aggregates in water and exhibited reversible morphological changes between sphere and nanofiber phases upon irradiation with UV and visible light,a sr eported in our previous work (Figure 1). [22] The photoinduced morphological change was causedb yp hotoisomerization of the diarylethenem olecules within the supramolecular architectures.…”
mentioning
confidence: 99%
See 1 more Smart Citation